Participatory ergonomics in Indonesian tin mining - Soejadi, Prijoko Prajitnoadi (2018)
Thousands of employees in small and medium-sized enterprises (SMEs) in Indonesia’s tin mining industry are working in dangerous environments without an adequate safety and health protection programme. Occupational safety (OS) has become a primary focal point when it comes to preventing dangerous incidents. Such incidents can lead to serious injuries and fatalities, particularly given that mining involves dangerous and high-risk activities, for example, in onshore tin mining, working in muddy areas with heat, humidity and a risk of landslide. Studies addressing the health and safety domain in Indonesia and the mining sector have the least number of ergonomics applications. The research examined the existing OS of a state-owned tin company, namely PT Timah, in Indonesia. The company has a relatively good level of experience in practising tin mining operations, and also employs occupational safety programmes. For approximately a decade, this company has collaborated with 16 private onshore SMEs which work in more than 400 locations under the PT Timah cooperation scheme. Despite applying OS and a health programme in the main company, the same programme has not been included in the tin mining operation cooperation scheme that regulates the rights and obligations of SMEs. This thesis examines the possibilities of using a well-established ergonomics approach and adapting it so that it is more frequently accepted and embraced in Indonesia. The research is focused on the participatory ergonomics (PE) approach as applied to SMEs. Postal data reviews, interviews and observation methods were used to examine the current status of OS in the Indonesian tin mining industry. The scenario-based design (SBD) method was used to investigate the acceptability of PE, while the two-round Delphi technique was applied to reach a consensus on the practical implementations of PE solutions. There is positive acceptance of PE among workers in Indonesian tin mining companies. Regular working safety dissemination through a kinship approach and specific safety training is recommended for resolving communication, cultural and knowledge issues related to OS. In addition to this, a consensus was reached on proposed solutions regarding the implementation of PE within the Indonesian tin mining industry, such as evaluation of the remuneration and bonus system, employing the train-the-trainer programme, and the OSH reporting system.